A validation study on the thermal simulation of the human body-clothing-environment system through wear trials. (September 2021) - Awais, Muhammad; Krzywinski, Sybille; Wölfling, Bianca-Michaela; Classen, Edith
The following analysis deals with the validation study for the already published thermal simulation of the human body-clothing-environment system through wear trials. Three test persons and a clothing system were selected for this study. The simulation process chain includes 3D scanning, clothing fit considering the deformation properties of fabrics, 3D analysis of air gaps between skin and clothing, and thermophysiological analysis of the human body taking into account different metabolic rates. Moreover, subjective wear trials were performed in a climatic chamber to validate the simulation results. The results show good validation for the core body and mean skin temperature, however, discrepancies were observed on comparing the local skin temperatures. The presented simulation approach offers a holistic solution for product development in the areas of sportswear, workwear, outdoor, and protective clothing.